1 / 16

160 likes | 258 Views

Solve the equation for y. STEP 1. x. y =. +. –. 9. 7. 4. 4. EXAMPLE 3. Rewrite a linear equation. Solve 9 x – 4 y = 7 for y . Then find the value of y when x = –5. SOLUTION. 9 x – 4 y = 7. Write original equation. – 4 y = 7 – 9 x. Subtract 9 x from each side.

Download Presentation
## EXAMPLE 3

**An Image/Link below is provided (as is) to download presentation**
Download Policy: Content on the Website is provided to you AS IS for your information and personal use and may not be sold / licensed / shared on other websites without getting consent from its author.
Content is provided to you AS IS for your information and personal use only.
Download presentation by click this link.
While downloading, if for some reason you are not able to download a presentation, the publisher may have deleted the file from their server.
During download, if you can't get a presentation, the file might be deleted by the publisher.

E N D

**Solve the equation for y.**STEP 1 x y = + – 9 7 4 4 EXAMPLE 3 Rewrite a linear equation Solve 9x – 4y = 7 for y. Then find the value ofywhen x= –5. SOLUTION 9x – 4y = 7 Write original equation. – 4y = 7 – 9x Subtract 9xfrom each side. Divide each side by –4.**(–5)**9(–5) – 4(– 13) 7 45 – y = – 4 y = + – 7 7 9 4 4 4 ? = EXAMPLE 3 Rewrite a linear equation Substitute the given value into the rewritten equation. STEP 2 Substitute –5 forx. Multiply. y = – 13 Simplify. CHECK 9x– 4y= 7 Write original equation. Substitute –5 for xand –13 for y. 7 = 7 Solution checks.**Solve the equation for y.**STEP 1 6 y = 2 + x EXAMPLE 4 Rewrite a nonlinear equation Solve 2y + xy = 6 for y. Then find the value of ywhen x= –3. SOLUTION 2y + x y = 6 Write original equation. (2+ x) y = 6 Distributive property Divide each side by ( 2 + x).**Substitute the given value into the rewritten equation.**STEP 2 6 y = 2 + (– 3) EXAMPLE 4 Rewrite a nonlinear equation Substitute –3 for x. y = –6 Simplify.**Solve the equation for y.**STEP 1 Substitute the given value into the rewritten equation. STEP 2 for Examples 3 and 4 GUIDED PRACTICE Solve the equation for y. Then find the value of ywhen x = 2. 8. y – 6x = 7 y – 6x = 7 y = 7 + 6x y = 7 + 6 (2) Substitute 2 forn. y = 7 + 12 Multiply. y = 19 Add.**19 – 6 (2) 7**? = for Examples 3 and 4 GUIDED PRACTICE CHECK y– 6x= 7 Write original equation. Substitute 2 for xand 19 for y. Solution checks. 7 = 7**Solve the equation for y.**STEP 1 + y = x 13 5 5 for Examples 3 and 4 GUIDED PRACTICE Solve the equation for y. Then find the value of ywhen x = 2. 9. 5y – x = 13 5y – x = 13 Write original equation 5y = 13 + x Add xto each side Divide each side by 5**5(5) – 2 7**+ y = 2 13 5 5 ? = for Examples 3 and 4 GUIDED PRACTICE Substitute the given value into the rewritten equation. STEP 2 Substitute 2 forn. y = 5 Simplify. CHECK 5y–x= 13 Write original equation. Substitute 2 for xand 19 for y. Solution checks. 3 = 3**Solve the equation for y.**STEP 1 3x 3x + y = 2 2 = – + 6 12 2 for Examples 3 and 4 GUIDED PRACTICE Solve the equation for y. Then find the value of ywhen x = 2. 10. 3x + 2y = 12 3x + 2y = 12 Write original equation 5y = 12 – 3x Subtract 3x from each side Divide each side by 2**– 3**6 6 + + y = y = 3(2) + 2(3) 12 – 2 (2) 2 2 ? = for Examples 3 and 4 GUIDED PRACTICE Substitute the given value into the rewritten equation. STEP 2 Substitute 2 forn. Multiply y = 3 Simplify CHECK 3x–yx= 12 Write original equation. Substitute 3 for yand 2 for x. 12 = 12 Solution checks.**Solve the equation for y.**STEP 1 2x 2x – y = 5 5 – = –1 –1 5 5 for Examples 3 and 4 GUIDED PRACTICE Solve the equation for y. Then find the value of ywhen x = 2. 11. 2x + 5y = –1 2x + 5y = –1 Write original equation 5y = –1 – 2x Subtract 2x from each side Divide each side by 5**4**2(2) – – y = y = 5 5 2(2) + 5(–1) –1 – 1 – 1 2 5 ? = for Examples 3 and 4 GUIDED PRACTICE Substitute the given value into the rewritten equation. STEP 2 Substitute 2 forn. Multiply y = – 1 Simplify CHECK 2x+ 5y= –1 Write original equation. Substitute 2 for xand –1 for y. –1 = –1 Solution checks.**Solve the equation for y.**STEP 1 3 +x = y 2x for Examples 3 and 4 GUIDED PRACTICE Solve the equation for y. Then find the value of ywhen x = 2. 12. 3 = 2xy – x 3 = 2xy – x Write original equation 3 + x = 2xy Add x to each side Divide 2x to each side**= y**1 = 1 y = 4 3 + 2 2 (2) 5 ( ) 4 5 4 Substitute 2 for xand 1 for y. 3 2(2) – (2) 5 4 ? = for Examples 3 and 4 GUIDED PRACTICE Substitute the given value into the rewritten equation. STEP 2 Substitute 2 forn. Simplify CHECK 3=2xy –x Write original equation. 3 = 3 Solution checks.**Solve the equation for y.**STEP 1 28 = y 4 – x for Examples 3 and 4 GUIDED PRACTICE Solve the equation for y. Then find the value of ywhen x = 2. 13. 4y – xy = 28 4y – xy = 28 Write original equation (4 – x)y = 28 Distributive property Divide each side by (4 – x)**y =**28 4 – 2 4(14) – (2) (14) 28 ? = for Examples 3 and 4 GUIDED PRACTICE Substitute the given value into the rewritten equation. STEP 2 Substitute 2 forx. y = 14 Simplify CHECK 4y –xy=28 Write original equation. Substitute 14 for yand 2 for y. 28 = 28 Solution checks.

More Related